2016
DOI: 10.1155/2016/8581421
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of Acute Myeloid Leukemia following Cisplatin Based Concurrent Therapy with Radiation for Squamous Cell Laryngeal Cancer

Abstract: Acute myeloid leukemia (AML) is a myeloid disorder with several established treatment regimens depending on patient and leukemic factors. Cisplatin is known to have strong leukemogenic potential and is rarely used even as salvage therapy in relapsed or refractory AML. We present a patient simultaneously diagnosed with AML and squamous cell carcinoma of the larynx, who was found to be in complete remission from AML following treatment with cisplatin based chemoradiotherapy for his laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We chose etoposide because it induces DNA damage and initiates p53 signaling 17 , 18 . In addition, cisplatin is a p53-dependent anticancer drug 19 , 20 , currently being used to treat refractory lymphomas and AML 21 24 . We found that only the high AIMP2-DX2-expressing HL-60 cells could be sensitized to etoposide and cisplatin via knockdown of AIMP2-DX2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We chose etoposide because it induces DNA damage and initiates p53 signaling 17 , 18 . In addition, cisplatin is a p53-dependent anticancer drug 19 , 20 , currently being used to treat refractory lymphomas and AML 21 24 . We found that only the high AIMP2-DX2-expressing HL-60 cells could be sensitized to etoposide and cisplatin via knockdown of AIMP2-DX2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The shielding effect of these proteins results in the poor repair of the cisplatin-modified DNA, thereby leading to activation of several signal transduction pathways (including those involving ATF, p53, p73, and MAPK) and ultimately cell apoptosis. 14,15 Anthracyclines, DNA-Intercalating Therapeutics of AML…”
Section: Deoxycytidine Analoguesmentioning
confidence: 99%
“…6,14,16 In this regard and as mentioned above, the alkaloid ester HHT in combination with the low-dose cytarabine and G-CSF (CHG regimen) exhibits considerable efficacy in patients with advanced MDS, t-AML, de novo and relapsed AML and in chronic myeloid leukemia. Noxa expression, and enhances the apoptotic response of AML cells, G1/S or G2/M transition blockage 9,29 in rational combination with docetaxel, doxorubicin, etoposide, and cisplatin shows additive or synergistic effects 15,24 Abbreviations: DNA Pol, DNA polymerase; DNMT, DNA methyltransferase; RNR, ribonucleotide reductase; dCK, deoxycytidine kinase; RAR, retinoic-acid-responsive; PRT, phosphoribosyl transferase; G-CSF, granulocyte colony-stimulating factor; HHT, homoharringtonine; DNPS, de novo purine synthesis; TOP I/II, topoisomerase I and II; ATRA, all-trans retinoic acid; RAR-RXR, retinoic acid receptor α-retinoid X receptor heterodimer protein; HDACs, histone deacetylases; HDACi, histone deacetylase inhibitors; HMTs, histone methyltransferases; Bad, BH3-only pro-apoptotic protein-encoding genes; TKs, tyrosine kinases.…”
Section: Deoxycytidine Analoguesmentioning
confidence: 99%